Association between azofert® and efficient microorganism potentiates the growth and productivity of beans - Hurtado, Alexander Calero [UNESP]; Rodríguez, Elieni Quintero; Díaz, Yanery Pérez; Hernández, Janet Jiménez; Lizazo, Iván Castro (Universidad del Zulia, 2020)
To evaluate the association between AzoFert® and efficient microorganisms (EM) in the morphological and productive response of common bean in three sowing season, three experiments were developed at the Collective farmer “Martires de Taguasco”, Sancti Spíritus, Cuba, from September 2014 to April 2015. The treatments evaluated were the absolute Control: without inoculating and without fertilizing, foliar applications of EM (100 mg.L-1), inoculation of the seeds with AzoFert® (108 cfu.g-1) and the associate between AzoFert® + EM. The indicators evaluated were: the height of the plants (cm), the number of leaves per plant, legumes per plant, grains per plant, mass of 100 grains (g) and yield (t.ha-1). The results showed that the treatments with EM, AzoFert® and the association between AzoFert® + EM achieved higher responses of the morphological and productive indicators on the intermediate sowing period (EI) in comparison to early (ET) and late season (EA). The AzoFert® + EM association treatments showed better performance compared with the individual application of EM and AzoFert® also increase the indicators evaluated and the yield was higher ~102 % in early season, ~113 % in the intermediate and 111 % in the late season in relationship to absolute control. The findings established the potentiality of the association of AzoFert® + ME as an efficient alternative to increase bean productivity and could potentially lead to sustained increase in crop yield.
Asociación entre azofert® y microorganismos eficientes como potenciadores del crecimiento y la productividad del frijol
Associação entre azofert® e microorganismos eficientes como potenciadores do crescimento e produtividade do feijão
Keywords: Biofertilizers; Crop yields; Foliar application; Phaseolus vulgaris; Rhizobium; Seed inoculation